Аналіз представлення популярних весільних фотографів у соціальних медіа - Барліт, Віталія; Березко, Олександр (Видавництво Львівської політехніки, 2019)
We consider online marketing approaches of popular wedding photographers based on the rating on mywed.com website. Two groups of photographers were formed – Ukrainian and international ones. Their online presence as well as behavior within general and niche social networking websites was analyzed.
Keywords: соціальні медіа; візуальна комунікація; онлайн-сервіси